Association of Cassava Consumption with Median Urinary Iodine Concentrations and Goiter Prevalence: A Pooled Analysis of 176 Countries. (29th May 2020) - Ssentongo, Paddy; Ba, Djibril; Pelton, Matt; Wisnousky, Holly; Lazzara, Nick; Ssentongo, Anna; Chinchilli, Vernon
Abstract: Objectives: Despite the universal iodization of salt in most parts of the world, iodine deficiency disorder remains a major public health problem, affecting over 2 billion people. Published literature on the association of over-consumption of cassava (a goitrogenic food) with lower urinary iodine concentration (UIC) and increased goiter prevalence are inconsistent. We aimed to examine the association of country-level cassava consumption with country-level median urinary iodine concentrations and goiter prevalence. Methods: We analyzed data on cassava consumption (kcal/capita/day) from the food and agriculture organization (FAO), median UIC, and goiter prevalence from the World Health Organization for 176 countries. We adjusted for country-level salt iodization rates. Meta-regression analysis was used to estimate the association of cassava consumption with median UIC and goiter prevalence. Results: The median UIC was: 171 μg/L; 25th and 75th percentile: 119–220). Median cassava consumption was 114 kcal/capita/day (25th and 75th percentile: 22–284). In the pooled multivariable-adjusted analysis, a 10-fold increase in salt iodization rate was significantly associated with a 157% increase in median UIC (β = 15.7, P = 0. 009. We found no association between cassava consumption and median UIC (β = −0.01, P = 0.90) or goiter prevalence (β = −0.005, P = 0.75). We consistently found no association between cassava consumption and the aforementioned outcomes in the subgroup of low and middle-income countries versus high-income countries and the lagged year of cassava consumption. Conclusions: In this ecological study, the consumption of iodized salt was associated with higher median UIC. We found no association of cassava consumption with reduced median UIC or increased goiter prevalence. Funding Sources: None.